Usability Engineering in the Prototyping Process of Software User Interfaces for Mobile Medical Ultrasound Devices - Wichrowski, Marcin (Computer Science, 2015)
This paper presents new trends in interface design of medical ultrasound devices and explains the basics of implementing usability engineering in accordance with international standards. Methods for determining the initial requirements, design guidelines, processes of prototyping, verification, and validation of software user interfaces for medical devices are discussed. The article also presents a preliminary plan of a methodology for prototyping touch-based and standard-control interfaces for mobile ultrasonic devices.